The philosophy behind self-managing work teams - Theo H. Veldsman (South African Journal of Business Management, 1995)
In recent times the work team, in contrast to the individual and his/her job, has been propagated as the most appropriate means around which to build the organization of the future. It is hoped that the use of the team as the basic building block of the future organization will release the desired synergy to meet the challenges posed by the new business order self-managing teams have been proposed as the pinnacle of the team-based organization. The purpose of this article is to discuss the philosophy behind self-managing work teams and indicate how they differ from traditional teams in organizations. Simultaneously an attempt is made to integrate the diverse literature on this concept in a conceptually sound but simple manner.
Keywords: 650